Influência de condições ambientais e tempo na recuperação de DNA de contato utilizando metodologia acessível - Pereira, Julia Del Piero (2023)
Fingerprints can configure a potential DNA source for genetic profiling in a forensic context. In this regard, the present study was conducted with 4 volunteers who made themselves available to produce fingerprints on previously sanitized plastic and wood surfaces, in order to leave touch DNA. The traces left on the objects were subjected to different variables: the incidence of direct and indirect sunlight, and the time between contact and collection of 24h and 72h. The collection was performed using a double swab and the DNA was extracted through organic extraction with phenol-chloroform. Then the material was quantified by NanoDrop, and the samples with the best income also passed through the Qubit fluorometer. Data were tabulated and submitted to statistical tests. The results showed that it is possible to obtain DNA from fingerprints left on plastic and wood surfaces, collected and extracted by accessible methods. The evaluated quantification methods were able to quantify the samples of interest, however the Qubit method showed greater specificity in relation to NanoDrop. It was possible to recover from 0 to 104 ng of DNA in the samples. Despite the statistical limitations and the absence of correlation, a greater DNA recovery was observed from impressions deposited on plastic, in relation to wood. Regarding the persistence of DNA until the moment of collection, a higher concentration of DNA with statistical significance was found in samples collected from wood, under indirect light and after 72 hours. While the other variables, exposure to direct sunlight, humidity and temperature, did not show a statistically significant effect. This information, along with future considerations, will contribute to increasing the forensic ability to produce interpretable DNA profiles during investigations, even when minimal biological traces are available.